Dengue-chikungunya infection in the tertiary care hospital of northern India: Cross-sectional latent class cluster analysis in viral infection - Gaurav Badoni; Puneet Kumar Gupta; Pratima Gupta; Neelam Kaistha; Yogendra Pratap Mathuria; Manju O. Pai; Ravi Kant (Heliyon, 2023)
Cases of dengue and chikungunya fever are escalating all over India. Both viruses share a common vector, the “Aedes” mosquito. Due to similar clinical symptoms, both the dengue (DENV) and chikungunya (CHIKV) virus can circulate as co-infection. There is very limited data available on dengue-chikungunya co-infection in Uttarakhand, India. The purpose of this study was to determine the seroprevalence of dengue and chikungunya virus infections, as well as their co-infection, in patients presenting with clinical symptoms. Serum samples of clinically suspected patients from the tertiary care hospital of Uttarakhand were collected, and Latent Class Cluster Analysis was performed for clinical profiling. ELISA was performed for DENV and CHIKV. 279 cases were enrolled, out of which 222 (79.5%) came positive for dengue NS1 Ag, 143 (51.2%) for dengue IgM, 98 (35.1%) for IgG followed by 16 (5.7%) of CHIKV IgM, and 4 (1.4%) were NS1 Ag with CHIKV IgM. Among the clinical features, fever (n = 270, 96.8%) was the most common symptom in all suspected dengue and chikungunya cases. Other symptoms like chills (n = 254, 91.0%), arthralgia (n = 241, 86.4%), and headache (n = 240, 86.0%) were present in a significant number. Results showed fewer odds of getting both DENV and CHIKV infection simultaneously, but the risk is still not negligible. This study explores the clinical presentation of the suspected dengue-chikungunya case. The increasing incidence of dengue and chikungunya and their co-infection necessitate the authorities' active surveillance of endemic regions and effective patient care management.